How effective are F-MARC injury prevention programs for soccer players? A systematic review and meta-analysis - Al Attar, W. S. A.; Soomro, N.; Pappas, E.; Sinclair, P. J.; Sanders, R. H. (Sports Medicine, 2016)
Background: The FIFA Medical and Research Centre (F-MARC) has designed a comprehensive warm-up program targeting muscular strength, body kinaesthetic awareness, and neuromuscular control during static and dynamic movements to decrease injury risk for soccer players. Prior studies have investigated the effectiveness of the F-MARC programs, but have not consistently reported a statistically significant reduction in injury and reduction in time loss due to injury from utilizing the program.